To a question of architecture of psychotherapy systems - Курило, Віталій Олексійович (Psychiatry, Neurology and Medical Psychology, 2019)
The task of the study was to analyze the problems of structuring a psychotherapeutic clinic and highlight the optimal structure of the stages of the psychotherapy system. To this end, a content analysis of existing ideas on the research topic was conducted. The results of the study demonstrate the state of psychotherapy as a clinical and scientific discipline in our time. The systematic use of contingent-specific combinations of psychotechnics determines the most relevant, at the moment, approach to structuring a psychotherapeutic clinic. Nevertheless, the issues of ergonomics and congruence both in relation to the object – the target contingent, and to the subject – the personality of the psychotherapist – receive the illumination only in separate studies. This list of conceptual studies sets is the general vector of methodological consolidation and disciplinary attribution of psychotherapy, transforming a disparate set of communicative practices, as it was at the beginning of the 21st century, into a clinical discipline that requires implementation of a systematic approach from the methodology that appeals to it. The study formulates the key questions, which are designed to determine the role and content of psychotherapy as a clinical discipline. The analysis of the existing systems of psychotherapy is carried out and their main features and global shortcomings are highlighted. The modern concept of the “psycho-phenomenological profile”, was designed to improve the psychotherapeutic process, was reviewed and analyzed. The optimal stages of the psychotherapy system and their components were highlighted.